Primary Metabolite Adjustments Associated With Pinewood Nematode Resistance in Pinus pinaster - Rodrigues, Ana M.; Carrasquinho, Isabel; António, Carla (Frontiers in Plant Science, 2021)
The pinewood nematode (PWN) Bursaphelenchus xylophilus is the causal agent of the pine wilt disease (PWD) and represents one of the major threats to conifer forests. The detection of the PWN in Portugal, associated with Pinus pinaster, increased the concern of its spread to European forests. Despite its susceptibility to PWD, genetic variability found among P. pinaster populations has been associated with heritable PWD resistance. Understanding the mechanisms underlying tree resistance constitutes a valuable resource for breeding programs towards more resilient forest plantations. This study investigated changes in anatomy, chlorophyll a fluorescence (ChlF), and primary metabolism in susceptible and resistant P. pinaster half-sib plants, after PWN inoculation. Susceptible plants showed a general shutdown of central metabolism, osmolyte accumulation, photosynthetic inhibition, and a decrease in the plant water status. The ChlF transient rise (OJIP curve) revealed the appearance of L- and K-bands, indicators of environmental stress. In contrast, resistant plants revealed a regulated defense response and were able to restrict PWN migration and cellular damage. Furthermore, the accumulation of γ-aminobutyric acid (GABA) and succinate suggested a role of these metabolites in PWD resistance and the possible activation of the GABA shunt. Altogether, these results provide new insights to the role of primary metabolism in PWD resistance and in the selection of resistant phenotypes for disease mitigation.